Antioxidant-Rich Diet, GSTP1 rs1871042 Polymorphism, and Gastric Cancer Risk in a Hospital-Based Case-Control Study - Kim, Jimi; Kim, Hyejin; Lee, Jeonghee; Choi, Il Ju; Kim, Young-Il; Kim, Jeongseon (Frontiers in Oncology, 2021)
Background Chronic gastritis along with Helicobacter pylori (H. pylori) infection has been implicated in inflammatory response-related genes linked to the causation of gastric cancer. Glutathione S-transferase Pi (GSTP1) plays a role in regulating oxidative stress and detoxification against carcinogenesis. In this study, we aimed to determine whether an antioxidant-rich diet is associated with gastric cancer risk and identify how this association could be altered by GSTP1 genetic variants. Methods This study included 1,245 participants (415 cases and 830 controls) matched for age and sex. The dietary antioxidant capacity was estimated based on the oxygen radical absorbance capacity (ORAC) incorporated with a semiquantitative food frequency questionnaire. Five single nucleotide polymorphisms (SNPs) of GSTP1 (rs1695, rs749174, rs1871042, rs4891, and rs947895) were selected among the exome array genotype data. Results High dietary ORAC was inversely associated with gastric cancer (hydrophilic ORAC OR T3 vs. T1, 95% CI = 0.57, 0.39-0.82, P = 0.004; lipophilic ORAC = 0.66, 0.45-0.95, P = 0.021; total phenolics = 0.57, 0.39-0.83, P = 0.005). The polymorphism rs1871042 increased the risk of gastric cancer (OR, 95% CI = 1.55, 1.10-2.16, P = 0.01, CT+TT vs. CC). A remarkably reduced risk of gastric cancer was observed among those who had a high dietary ORAC according to rs1871042 polymorphism (hydrophilic ORAC OR T3 vs. T1, 95% CI = 0.36, 0.17-0.78, P for trend = 0.013; lipophilic ORAC = 0.58, 0.37-0.93, P for trend = 0.021; total phenolics = 0.38, 0.17-0.83, P for trend = 0.019). Conclusions Our findings indicate that dietary ORAC intake may be inversely associated with the risk of gastric cancer altered by genetic variants of GSTP1, providing new intervention strategies for gastric cancer patients.